Impact of social network on cardiovascular mortality in middle aged Danish men. Issue 3 (June 1993) - Olsen, O
Abstract : STUDY OBJECTIVE–To estimate quantitatively (the aetiological fraction) the impact of poor social network on premature death from cardiovascular disease in middle aged, white men. DESIGN–The causality of the relationship has already been discussed in a large review, and it is assumed to be well documented. The numerical estimation of the impact was based on a review of all published cohort studies on the relationship between social network and mortality in white, middle aged men. RESULTS–The studies reviewed are all of high epidemiological quality and present a consistent and stable dose-response pattern. The aetiological fraction was estimated to be 30%, with a plausible range of 20-40%. CONCLUSIONS–Social network was an important, independent, risk factor for cardiovascular disease in white, middle aged men. It had a strong impact on mortality, comparable to that of traditional risk factors. Social network should have a more central role in future epidemiological research into cardiovascular disease. The factors that result in a strong social network should be identified and strategies applicable in preventive work should be developed.